COMMUNITY SERVICE BASED ON SCIENTIFIC WORK (PKM KI): IMPROVING STUDENT CHARACTER THROUGH PUBLIC SPEAKING AT MI DARUL FALAH - Al - Banjari, Faisal; Muhammad , Rijal Habib; Santoso, Hajizah Indah; Andini, Irda; Sari , Novita; Wahab , Wahab (PT. Hafasy Dwi Nawasena, 2025)
This Community Service Based on Scientific Work (PKM-KI) was motivated by the lack of communication skills and self-confidence among primary school students in public speaking. The program aims to strengthen students character through Islamic public speaking training at MI Darul Falah. The study applied a descriptive qualitative method with a participatory educational approach, involving 30 students from grades IV to VI. The training consisted of theoretical sessions, practical speaking exercises, and mentoring conducted by lecturers and teachers. The results indicated a significant improvement in students confidence, responsibility, and politeness in communication. Students become more capable of expressing ideas logically and respectfully. It can be concluded that Islamic-based public speaking effectively reinforces core character values ​​such as empathy, integrity, and responsibility. It is recommended that this program be sustained as a flagship initiative for character education in Islamic and primary schools